A noticeable effect of Pr doping on key optoelectrical properties of CdS thin films prepared using spray pyrolysis technique for high-performance photodetector applications. Issue 4 (March 2020) - Shkir, Mohd.; Ashraf, I.M.; AlFaify, S.; El-Toni, Ahmed Mohamed; Ahmed, Mukhtar; Khan, Aslam
Abstract: High-quality thin film-based photodetectors containing praseodymium doped cadmium sulfide (Pr:CdS) were fabricated through spray pyrolysis and studied for various opto-electrical applications. Field emission electron microscopy (FE-SEM) revealed that the prepared films were highly compacted with an extremely fine nanostructure without any pinhole or crack. X-ray diffraction and FT-Raman spectroscopy studies confirmed the single hexagonal phase of all the films. The crystallite size was found to lie between 19 and 32 nm. Optical spectroscopy revealed that the fabricated films have low absorbance and high transmittance (in range of 70–80%). The energy gap was found to lie in the range of 2.40–2.44 eV. The PL spectra contained an intense green emission band at 531 ± 5 nm (2.33 eV), and its intensity was enhanced by increasing the Pr doping content in CdS. The dark and photo currents of CdS increased by approximately 950 and 42 times, respectively with the addition of 5.0 wt% Pr. The responsivity (R) and specific detectivity (D*) were remarkably enhanced to 2.71 AW -1 and 6.9 × 10 11 Jones, respectively, for the 5.0 wt% Pr:CdS film. The external quantum efficiency (EQE) of 5 wt% Pr:CdS films was 43 times that of pure CdS films, and the on/off ratio was 3.95 × 10 2 for 5.0 wt% Pr:CdS film. Its high R, D*, and EQE values, and photo-switching behavior make Pr:CdS a good contender for high quality photodetector applications.